Decolonialidad e interculturalidad crítica: Teoría y praxis desde los territorios en Latinoamérica - Pincheira Muñoz, Luis; López Noreña, Germán (Ariadna Ediciones, 2024)
The compilation of this publication on Decoloniality and Critical Interculturality: Theory and Praxis from the Territories in Latin America, is the fruit of practical experiences and theoretical reflections of its members from the line of research Decoloniality other knowledge, feelings and thinking from ABYA YALA, which aims to disseminate knowledge of sociocultural relations and practices, whose epistemological, ontological and ethical principles from critical decolonial Intercultural education, assumes the commitment to reflect on the multiplicity of themes from theoretical aspects and practical experiences as a space for sociocultural transformation, which ancestral cultures and Latin American cultures contribute from the different territories. The line of research belonging to the Foundation Network of Educators for Ibero-America seeks to disseminate and make visible these contributions.